A two-dimensional MXene/BN van der Waals heterostructure as an anode material for lithium-ion batteries. Issue 22 (25th May 2022) - Yuan, Kun; Hao, Pengju; Zhou, Yang; Hu, Xianchao; Zhang, Jianbo; Zhong, Shengwen
Abstract : A q-Ti3 C2 T x /BNNS heterostructure was prepared by means of high energy ball-milling, and exhibited a long-term cycling stability with 84.4% capacity retention after 1400 cycles at 0.5 A g −1 . Abstract : Titanium carbide (Ti3 C2 T x ) is highly regarded as a promising anode material for lithium-ion batteries but suffers from sluggish kinetics with low storage capacity. In this work, a BN/Ti3 C2 T x heterostructure is effectively fabricated by high energy ball-milling, which plays a series of roles in enlarging the interlayer spacing, reducing the size of the nanosheets and maintaining the structural integrity. Benefiting from the synergistic effect between the BN and Ti3 C2 T x monolayers, it delivers a high reversible capacity of 521.6 mA h g −1 at 0.1 A g −1, excellent rate capabilities (344.9 mA h g −1 at 1 A g −1 and 251.3 mA h g −1 at 2.5 A g −1 ) and a robust long-term cycling stability with 84.4% capacity retention after 1400 cycles. In particular, the theoretical calculations further confirm that the BN/Ti3 C2 T x heterostructure manifests improved adsorption energies, an ultralow diffusion barrier and a high charge–discharge rate. These findings provide an important new strategy for further design and rational fabrication of MXenes for energy storage applications.